A multisampling time-domain CMOS imager with synchronous readout circuit - Campos, Fernando de Souza [UNESP]; Marinov, Ognian; Faramarzpour, Naser; Saffih, Faycal; Deen, M. Jamal; Swart, Jacobus W. (Springer, 2008)
A novel multisampling time-domain architecture for CMOS imagers with synchronous readout and wide dynamic range is proposed. The proposed multisampling architecture requires only a single bit per pixel memory instead of 8 bits which is typical for time-domain active pixel architectures. The goal is to obtain a time-domain imager with high dynamic range that requires lower number of transistors per pixel in order to achieve higher fill-factor. The maximum frame rate is analyzed as a function of number of bits and array size. The analysis shows that it is possible to achieve high frame rates and operate in video mode having 10 bit pixel data resolution. Also, we present analysis of the impact of comparator offset voltage on the fixed pattern noise. The architecture was implemented in an imager prototype with 32 x 32 pixel array fabricated in AMS CMOS 0.35 mu m and was characterized for sensitivity, noise and color response. The pixel size is 30 mu m x 26 mu m and it is composed of an n+/psub photodiode, a comparator and a D flip-flop with a 16% fill-factor.
Keywords: active pixel sensor; dynamic range; fill-factor; CMOS imager